2003
DOI: 10.1029/2001je001638
|View full text |Cite
|
Sign up to set email alerts
|

Topographically induced north‐south asymmetry of the meridional circulation in the Martian atmosphere

Abstract: [1] A Martian atmospheric general circulation model is developed to investigate the effect of topographic elevation in the meridional circulation of the Martian atmosphere. It is confirmed that, even at equinoxes, the meridional circulation below $20 km altitude has an asymmetric pattern with respect to the equator. Sensitivity experiments reveal that the topographic elevation difference between the northern and southern hemispheres is the most dominant factor for producing such an asymmetric circulation. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 39 publications
(57 reference statements)
3
31
0
Order By: Relevance
“…In both solstices the characteristic meridional circulation on Mars exists, which flows across the equator from summer hemisphere to winter hemisphere. It also shows that the circulation is 2@3 times stronger in southern summer than in northern summer, which is consistent with the results of other Martian GCMs Forget et al 1999;Richardson and Wilson 2002;Takahashi et al 2003). The sources of this phenomenon seem to be not only the difference of the amount of insolation as mentioned in Section 1, but also the effects of Martian topography which …”
Section: Numerical Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In both solstices the characteristic meridional circulation on Mars exists, which flows across the equator from summer hemisphere to winter hemisphere. It also shows that the circulation is 2@3 times stronger in southern summer than in northern summer, which is consistent with the results of other Martian GCMs Forget et al 1999;Richardson and Wilson 2002;Takahashi et al 2003). The sources of this phenomenon seem to be not only the difference of the amount of insolation as mentioned in Section 1, but also the effects of Martian topography which …”
Section: Numerical Resultssupporting
confidence: 80%
“…In both equinoxes the profile is near a symmetric circulation with respect to the equator, though below the altitude of 1 hPa an asymmetric pattern with respect to the equator exists, which the intensity of northern circulation is stronger than that of southern circulation. This asymmetric pattern seems to be caused dominantly by the topographic elevation difference between northern and southern hemisphere (Takahashi et al 2003). In both solstices the characteristic meridional circulation on Mars exists, which flows across the equator from summer hemisphere to winter hemisphere.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…They then showed that this bias was essentially eliminated if the hemispheric dichotomy in topography was removed. Takahashi et al (2003) have explored this further, and shown a similar dependence on the elevated southern hemisphere using another Mars general circulation model. Such biases can be most easily investigated for e = 0, since for a featureless and smooth planet this situation would produce mirror image circulations at the two solstices as well as a highly symmetric mass streamfunction when averaged over the entire year.…”
Section: The Atmospheric Circulationmentioning
confidence: 82%
“…Recent studies investigated the role of the topographic asymmetry (northern lowlands, southern highlands) on the Hadley circulation (Richardson and Wilson, 2002;Takahashi et al, 2003), the role of dust with an active dust module in the AOPP/LMD model (Newman et al, 2002), and the thermal circulation over a Martian volcano with a mesoscale model (Rafkin et al, 2002). Most similar to what is attempted here, a paleo study investigating the impact of orbital parameters mainly on dust lifting potential has been performed with the AMES model (Haberle et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…The more recent successful orbiter missions, Mars Global Surveyor (MGS, launched 1996), and Mars Odyssey (launched 2001) and now Mars Express (2003) have brought a new wealth of observational data that will boost the numerical model development. Established modelling groups work at LMD, Paris and AOPP, Oxford on the European GCM (Read et al, 1997;Forget et al, 1999), at the NASA/Ames research center in Moffett Field on the NASA AMES GCM , at Princeton, New Jersey and Caltech, Pasadena on the 'SKYHI' model (Wilson and Hamilton, 1996), and at distributed institutes in Japan (Takahashi et al, 2003). The models, all derivatives of Earth General Circulation Models (GCMs), solve the equations of fluid dynamics and include the processes of radiative transfer, cloud formation, regolith-atmosphere water exchange, and advective transport of dust and trace gases.…”
Section: Introductionmentioning
confidence: 99%